2003
DOI: 10.1055/s-2003-37756
|View full text |Cite
|
Sign up to set email alerts
|

Beeinflusst Akupunktur die autonom kardiale Regulation bei Patienten mit leichten depressiven Episoden oder Angststörungen?

Abstract: We undertook this study to evaluate the effects of needle acupuncture on cardiac autonomic nervous system (ANS) function in patients with minor depression or anxiety disorder. Patients (n = 36) were randomly distributed into a verum acupuncture (VA) group (needles were applied at classical acupuncture points, e. g. He7, Pe6, Du20, Bl62, Ex6) or a placebo (PL) group (needles were applied only epidermal at non-acupuncture points). Both groups underwent standardized measurements of the 5-minute resting heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In the third paper from 2001, Sakai et al [16] included HRV in a general concept of behavioural health services, and the authors reported HRV as a useful parameter. In 2003, Agelink et al [17] also undertook a study to evaluate the effects of needle acupuncture on cardiac autonomic nervous system function in patients with minor depression or anxiety disorders. In contrast to our 22 patients, the 36 patients from that group were randomly distributed into a verum acupuncture group and a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…In the third paper from 2001, Sakai et al [16] included HRV in a general concept of behavioural health services, and the authors reported HRV as a useful parameter. In 2003, Agelink et al [17] also undertook a study to evaluate the effects of needle acupuncture on cardiac autonomic nervous system function in patients with minor depression or anxiety disorders. In contrast to our 22 patients, the 36 patients from that group were randomly distributed into a verum acupuncture group and a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3). In the study by Agelink et al [19], this effect was only significant in verum acupuncture in patients with minor depression or anxiety. Therefore, a relative increase of cardiovagal modulation of heart rate and physiological regulatory effects due to acupuncture stimulation could be detected in the present study, which confirms the results of other authors [19], although the acupuncture schemes were different (He.7 Shenmen and PC7 Neiguan [19] versus PC5 Jianshi [2] and GV20 Baihui (this study)).…”
Section: Discussionmentioning
confidence: 95%
“…In the third paper in 2001, Sakai et al [18] included HRV in a general concept of behavioural health services, and the authors reported HRV as a useful parameter. In 2003, Agelink et al [19] also undertook a study to evaluate the effects of needle acupuncture on cardiac autonomic nervous system function in patients with minor depression or anxiety disorders. In contrast to our 33 patients, the 36 patients from that group were randomly distributed into a verum acupuncture group and a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been seen as a complex but tolerable non-pharmacological intervention [34]. The effects of acupuncture on psychological distress are not fully understood, but according to studies [67,68], these symptoms generally depend on disorders of the autonomic cardiac control system, with excess sympathetic and reduced parasympathetic regulation. General mental health improvement depends on multiple factors, including acupuncture’s anxiety-relieving effects [41,44], which are of the greatest value [67,68]; moreover, the clinical effects on the autonomic nervous system have been confirmed [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of acupuncture on psychological distress are not fully understood, but according to studies [67,68], these symptoms generally depend on disorders of the autonomic cardiac control system, with excess sympathetic and reduced parasympathetic regulation. General mental health improvement depends on multiple factors, including acupuncture’s anxiety-relieving effects [41,44], which are of the greatest value [67,68]; moreover, the clinical effects on the autonomic nervous system have been confirmed [69,70]. The relationship between the autonomic cardiac control system and acupuncture could help to explain the mechanism of acupuncture’s effects on treating psychological distress [71], and in the relationship between SOC and cardiac autonomic activity, a higher SOC score was positively correlated with parasympathetic regulation [72].…”
Section: Discussionmentioning
confidence: 99%